2019
DOI: 10.1002/qj.3605
|View full text |Cite
|
Sign up to set email alerts
|

Wind turning in the atmospheric boundary layer over land

Abstract: A climatology of the boundary‐layer wind‐turning angle over land is presented based on radiosonde observations from 800 stations in the Integrated Global Radiosonde Archive (IGRA). The dependence of the wind turning on a suite of parameters is analyzed. Results from previous studies indicating the importance of the planetary boundary layer (PBL) stratification for the angle of wind turning are confirmed here. A clear increase in the wind‐turning angle with wind speed, particularly for stratified conditions, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Veering and backing inflow are characteristic nighttime situations of the boundary layer flow if no other processes such as topographically induced circulations or large-scale weather systems prevent the establishment of an SBL regime. Veer within the wind-turbine rotor layer has been observed with several field campaigns with towers and lidars (Walter et al, 2009;Sanchez Gomez and Lundquist, 2020;Bodini et al, 2019Bodini et al, , 2020, and veer throughout the boundary layer has been observed globally using radiosonde datasets (Lindvall and Svensson, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veering and backing inflow are characteristic nighttime situations of the boundary layer flow if no other processes such as topographically induced circulations or large-scale weather systems prevent the establishment of an SBL regime. Veer within the wind-turbine rotor layer has been observed with several field campaigns with towers and lidars (Walter et al, 2009;Sanchez Gomez and Lundquist, 2020;Bodini et al, 2019Bodini et al, , 2020, and veer throughout the boundary layer has been observed globally using radiosonde datasets (Lindvall and Svensson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a convective regime during the daytime above the surface layer, there is no significant change in the incoming wind direction or wind speed with height and the inflow conditions are uniform over the whole rotor area. A nocturnal stably stratified regime, however, often generates wind profiles with changing magnitude (vertical wind shear) and direction (wind veer; Lindvall and Svensson, 2019). Vertical variations in both quantities reflect the balance between Coriolis force and friction.…”
Section: Introductionmentioning
confidence: 99%
“…Shu et al [37] examined the dependence of the wind veer profile on upstream terrain conditions and mean wind speed. Lindvall and Svensson [38] reported that there is clear latitudinal dependence of wind veer, with angles increasing with latitude. Moreover, seasonal and diurnal cycles are also apparent, which is mostly related to the variations in thermal stratification.…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the wind field within the boundary layer, observational studies that are based on campaigns limited to a few days report a large range of values for the wind turning angle with small values up to 10-15 degrees for convective conditions [2] and larger values reaching up to 35 degrees for stable boundary layers [45]. Lindvall and Svensson [26] derived a forty-year global climatology for the wind turning angle using the IGRA sounding data set. They found a strong dependence of turning angle with latitude, so for the range of latitudes of the three sites in our study they found a slight veering of the wind with a median value for the global average of the wind turning angle of 15 degrees with little seasonal variation.…”
Section: Comparison To Results From Previous Studiesmentioning
confidence: 99%
“…In this study, we expand the climatology over a period of 32 years and over two additional sites in Greece. In addition, climatologies of the wind field have recently been reported on a global scale [26] but this study focuses on the region of Greece.…”
Section: Introductionmentioning
confidence: 99%